PENANGGUHAN UPAH (UJRAH) MENURUT HUKUM AKAD SYARIAH - Aqly Mubarak (AL-IBANAH, 2022)
Wages come from the Arabic word that is ujrah. In terms of the language of al-ajru is ‘iwad or replace the word al-ajru or ujrah according to the language means al-iwad, that is to replace, in other words the provision of wages or rewards is a sign of action. Islam gives direction that the transfer of salary or wages is done when the work is completed. In this case the worker is required to speed up his work or service to his employer, while as an employer must speed up his payment to workers or payment of workers' wages. Wages should be given according to a contract that was previously agreed upon or in accordance with an employment contract, because the existence of the contract will create cooperation between the worker and his employer and contain the rights to the obligations of each party. If an agreement or contract is not reached then in case accelerate or suspend wages in this case wages are associated with a certain time then must be met when due. Keywords: Wages, workers, employers, contracts.